The Relationship Between Insomnia and Suicidal Behavior in Adolescents at SMAN 11 Mataram - Astika, Nensy Dwi; Diatmika, I Putu; Elizar, Lale Justin Amelinda; Syamsun, Arfi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Adolescence is a vulnerable period for mental health problems, including suicidal behavior. Insomnia is frequently experienced by adolescents and may be associated with emotional dysregulation and psychological distress. This intention of this study was to analyze relationship between insomnia and suicidal behavior among adolescents at SMAN 11 Mataram. This analytical observational study used a cross-sectional design involving 89 students of SMAN 11 Mataram. The sample size was determined using the Slovin from a population of 113 students with a 5% margin of error. Sampling was conducted using stratified random sampling based on grade level: grade 10(29 students), grade 11(36 students), and grade 12(48 students), with proportional random selection resulting in 23, 28, and 37 students, respectively. Data were collected using the validated Indonesian version of the Insomnia Severity Index (ISI) and Suicide Behaviors Questionnaire-Revised (SBQ-R). Insomnia was categorized based on ISI score ≥10, while suicidal behavior risk was identified using SBQ-R score ≥7. Reliability analysis showed Cronbach’s alpha values of 0.750 for ISI and 0.896 for SBQ-R.Spearman’s rank correlation test showed a significant association between insomnia and suicidal behavior (r = 0.229; p = 0.031). It was concluded there is a positive association between insomnia and suicidal with a weak correlation.